Dark current suppression of amorphous selenium based photosensors by the ZnO hole blocking layer - Yu, Tung-Yuan; Pan, Fu-Ming; Chang, Cheng-Yi; Hu, Tien; Chen, Jenn-Fang; Wang, Jia-Feng; Lin, Cheng-Lu; Chen, Tsung-Han; Chen, Te-Ming (Current applied physics, 2014)
To study the influence of defects in the hole blocking layer (HBL) on the dark current of amorphous selenium (a-Se) based photosensors, we prepared ZnO thin films by reactive sputter deposition (RSD) for the use as the HBL of the photosensors. The ZnO HBL layers prepared with different oxygen flow rates were characterized by X-ray photoelectron spectroscopy, Raman scattering analysis and photoluminescence, indicating that the density of oxygen vacancies in the ZnO thin films is significantly affected by the oxygen flow rate. The deep level transient spectroscopy measurement reveals two hole trap levels present in the RSD deposited ZnO thin films; one is at 0.94 eV and the other at 0.24 eV above the valence band edge. The electrical performance of the a-Se photosensor is largely influenced by the amount of oxygen vacancies in the ZnO thin film. The a-Se photosensor with the ZnO HBL of the most oxygen vacancies has the lowest dark current and demonstrates the highest breakdown field. •ZnO film was prepared for the use as the hole blocking layer in a-Se photosensors.•Material and electrical analyses related oxygen vacancies with hole traps in ZnO.•Dark current of a-Se photosensors depends on the oxygen vacancy density in ZnO.